1995
DOI: 10.1111/j.1365-2273.1995.tb00007.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of topical corticosteroid powder for nasal polyps: a double-blind, placebo-controlled study of budesonide

Abstract: Budesonide has been used for a number of years as a topical nasal corticosteroid in the treatment of nasal allergy and nasal polyps. Recently, a new device for powder insufflation where no constituents or preservatives are included has been developed (Rhinocort Turbuhaler, Astra Draco AB, Sweden). The present investigation was designed in order to study the efficacy of topical budesonide powder as the only treatment of nasal polyps. A total of 126 patients entered the study. The medical history and clinical re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
150
1
4

Year Published

1997
1997
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(158 citation statements)
references
References 11 publications
(1 reference statement)
1
150
1
4
Order By: Relevance
“…Treatment of NP consists of medical and/or surgical treatment. Topical glucocorticosteroid therapy has a well established role in the management of NP, since it has proven efficacy on symptoms and size of polyps and may help prevent the recurrence of NP after surgery (40). Surgical management Difficult asthma of NP aims to restore normal nasal function, including nasal ventilation and sinus drainage, when topical GCS alone are insufficient.…”
Section: Upper Airway Diseasesmentioning
confidence: 99%
“…Treatment of NP consists of medical and/or surgical treatment. Topical glucocorticosteroid therapy has a well established role in the management of NP, since it has proven efficacy on symptoms and size of polyps and may help prevent the recurrence of NP after surgery (40). Surgical management Difficult asthma of NP aims to restore normal nasal function, including nasal ventilation and sinus drainage, when topical GCS alone are insufficient.…”
Section: Upper Airway Diseasesmentioning
confidence: 99%
“…93 To date, however, there have been only a few published studies focusing on INS treatment outcomes in nasal polyposis. Small short-term studies from the 1990s examined the use of aqueous and powder forms of budesonide [97][98][99] and found it to be efficacious in the treatment of small-to largesized polyps. Other studies in patients with severe or bilateral polyposis found evidence of similar efficacy and tolerability of fluticasone propionate or beclomethasone dipropionate, with some evidence that fluticasone had a more rapid onset of action.…”
Section: Acute Rhinosinusitis and Nasal Polyposis: Association With Amentioning
confidence: 99%
“…The topic corticosteroid therapy is a well-established part in the treatment of allergic rhinitis [15] and chronic sinusitis [16,17]. Mometasone nasal spray showed the greatest effectiveness in reducing fibroblast cultures in nasal polyps followed by beclomethasone [18].…”
Section: Discussionmentioning
confidence: 99%